“Ignoring” to “Autonomous” Participation: Narratives of a Participatory Action Researcher - Pant, Binod Prasad; Luitel, Bal Chandra; Gjøtterud, Sigrid; Bjønness, Birgitte (The Canadian Journal of Action Research, 2023)
This paper examines different layers of participation while conducting Participatory Action Research (PAR). In the journey of three years of fieldwork with teachers, many realizations were made about becoming co-researchers and engaging in a collaborative knowledge-building process for developing an engaged pedagogical approach. The paper had two purposes: a) exploring the different layers of participation in PAR, and b) documenting the lead researcher’s continuous professional learning in understanding PAR. The lead researcher proposed “ignoring” to “autonomous” participation as levels. The lead researcher also changed from overly influencing roles on PAR to accepting co-researchers' voices and respecting their efforts for sustainable change.